The Impact of Marketing Mix on Indigenous Business Development in Uzbekistan: A Regression Analysis - Khilola, Yulchieva; Jibril, Abdul Bashiru (Journal of Intelligent Communication, 2024)
This study proposes a marketing strategy framework tailored to address the challenges faced by small and medium-sized enterprises (SMEs) in Uzbekistan. Amidst a fiercely competitive business landscape, SMEs encounter obstacles in establishing brand awareness, attracting customers, and optimizing financial performance. To address these challenges and sustain growth, SMEs can leverage the extended marketing mix, encompassing product, price, place, promotion, people, process, and physical evidence. Employing a combination of descriptive and exploratory research methodologies, this study utilizes quantitative data-gathering techniques, including a survey of entrepreneurs’ perspectives on the implementation of marketing mix strategies by SMEs. Regression analysis, facilitated by STATA software, examines the correlation between marketing mix variables and SME development. Key findings underscore the importance of integrating marketing mix elements to enhance SME marketing efforts, cultivate brand loyalty, and gain a competitive advantage. These findings contribute to a deeper understanding of marketing strategies for SMEs in developing economies like Uzbekistan, offering actionable insights for policymakers and entrepreneurs alike to foster SME growth and economic development.